2006
DOI: 10.1016/j.brainresrev.2006.01.002
|View full text |Cite
|
Sign up to set email alerts
|

A meta-regression to examine the relationship between aerobic fitness and cognitive performance

Abstract: Many studies have been conducted to test the potentially beneficial effects of physical activity on cognition. The results of meta-analytic reviews of this literature suggest that there is a positive association between participation in physical activity and cognitive performance. The design of past research demonstrates the tacit assumption that changes in aerobic fitness contribute to the changes in cognitive performance. Therefore, the purpose of this meta-analysis was to use meta-regression techniques to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
412
6
26

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 607 publications
(487 citation statements)
references
References 69 publications
30
412
6
26
Order By: Relevance
“…In general, the training group improved more in their mental control, sustained attention, immediate memory, verbal working memory, response speed, visuomotor coordination, visuospatial constructional ability, visual memory and learning, episodic memory, short-and long-term memory, executive functioning, reaction speed, and accuracy in executing simple tasks compared to the other groups. These results are in agreement with the findings of several reports of improved neuropsychological functioning in individuals who participate in regular physical exercise, and they suggest that a program that constitutes physical exercise could be used to improve neuropsychological aspects in older adults (Etnier et al 2006).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In general, the training group improved more in their mental control, sustained attention, immediate memory, verbal working memory, response speed, visuomotor coordination, visuospatial constructional ability, visual memory and learning, episodic memory, short-and long-term memory, executive functioning, reaction speed, and accuracy in executing simple tasks compared to the other groups. These results are in agreement with the findings of several reports of improved neuropsychological functioning in individuals who participate in regular physical exercise, and they suggest that a program that constitutes physical exercise could be used to improve neuropsychological aspects in older adults (Etnier et al 2006).…”
Section: Discussionsupporting
confidence: 92%
“…However, a growing body of literature suggests that age-related declines in neuropsychological aspects can be reduced by using alternative interventions, such as physical exercise (Etnier et al 2006;Colcombe and Kramer 2003;Kravitz et al 2012). Furthermore, physical exercise reduces the risk of diseases that impair neuropsychological functions, such as hypertension, diabetes, and cardiovascular disease (Anstey and Christensen 2000;Lacza and Radák 2013).…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies 4, [15][16][17][18] have reported that physical fitness confers significant benefits on cognitive function and memory in young adults and in independent older subjects, the current study demonstrated that physical activity can significantly improve cognitive and frontal lobe function in semi-independent elderly individuals, including the physically frail.…”
Section: ⅳ.Discussioncontrasting
confidence: 60%
“…These results corroborate previous findings demonstrating effects of exercise on cognitive and frontal lobe function in healthy elderly subjects. A meta-analysis by Etnier et al 16) found that only four studies in the literature included subjects with a mean age over 70 years, and that among these studies the oldest subjects had a mean age of 73 years. Lautenschlager et al 17) also suggested that there are insufficient data on the effects of exercise in latter-stage elderly subjects.…”
Section: ⅳ.Discussionmentioning
confidence: 99%
“…Many studies have been conducted in adults to test the potentially beneficial effects of increases in cardiorespiratory fitness on cognition. 88 However, similar information in young people is lacking. Recently, it has been reported that physical fitness, especially cardiorespiratory fitness, seems to be positively related to academic performance (that is, mathematics, reading and overall performance) in youths.…”
Section: Physical Fitness and Mental Healthmentioning
confidence: 99%